THE IMPLEMENTATION OF PROBLEM POSING WITH FERRIS WHEEL HYDROLYSIS TO IMPROVE SCIENCE PROCESS SKILLS - Ahsani, Mar’atuzzakiya; Utami, Annisa; Febriyanti, Resi; Enawaty, Eny (Universitas Tanjungpura, 2021)
This study aims to determine the students’ science process skills towards Salt Hydrolysis material in class XI IPA of SMA Katolik Talino Ambawang before and after being given the problem-posing learning model by using Ferris wheel hydrolysis and how much it improves the skills. It is a pre-experimental study with a one-group pretest-posttest design. The sampling technique used is saturated sampling, of which the subjects are 12 students of XI IPA. The normality test used on the pretest and posttest results is the Shapiro-Wilk test, which results in a normal distribution, Asymp.Sig. (2-tailed) greater than 0,05 with a significance pretest of 0,197 and postest of 0,547. The t-test results of the pairing sample indicate that the Asymp. Sig. (2-tailed) value is less than 0.05, which is 0,000 < 0.05. It was concluded that there is a difference between the students’ science process before and after the treatment. The mean scores of the students’ skills before and after the treatment are respectively 45,69% and 82,36%, with a high category. The value of 0,68 from the N-Gain calculation showed that the problem-posing learning model using Ferris wheel hydrolysis on Salt Hydrolysis material improved the students’ skills with the medium category.